Modelo de referencia para gerenciamento de empresas de serviços de montagem mecânica - Kleveston, Olavo Luiz (2016)
This dissertation was developed due to intense global competition that currently exists between companies, relevance of the service sector in the world economy and the need to make available to the manufacturers of capital goods, a management tool. The aim is to thereby improve the management of the outsourcing process, proposing a reference mo del for management of mechanical assembly services companies, increasing the competence of companies and at the same time making more firm and flexible structures. This study reviews the literature on the main concepts related to services, outsourcing, business management, qualification and assessment of suppliers, modeling software and also the most recent work in the area of management services companies. Thus, based on the concepts studied, there is the importance of adopting strategic actions that reflect the needs of the relationship b etween the manufacturer of capital goods, services and the end customer. Therefore, this study focused on the definition of the model requirements, specify its architecture, develop it, demonstrate its concept from the use of modeling software and finally illustrate with practical application of the reference model. Finally, it is concluded that the development of this model is a most important tool to assist in the management of outsourced companies because amplifies the manager's vision and influence on quality of service and profitability. The methods used to demonstrate the model with the use of information technology, is also presented in the study.